2015
DOI: 10.1117/1.jpe.5.057607
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in light outcoupling from white organic light-emitting diodes

Abstract: Organic light-emitting diodes (OLEDs) have been successfully introduced to the smartphone display market and have geared up to become contenders for applications in general illumination where they promise to combine efficient generation of white light with excellent color quality, glare-free illumination, and highly attractive designs. Device efficiency is the key requirement for such white OLEDs, not only from a sustainability perspective, but also because at the high brightness required for general illuminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
129
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(130 citation statements)
references
References 97 publications
(80 reference statements)
1
129
0
Order By: Relevance
“…This is especially important in top-emitting devices where the cathode is composed of a thin semitransparent metal layer such as Ag. The device efficiency can be doubled [15] by applying additional light out-coupling measures.…”
Section: Properties Of State Of the Art Organic Light Emitting Diodesmentioning
confidence: 99%
“…This is especially important in top-emitting devices where the cathode is composed of a thin semitransparent metal layer such as Ag. The device efficiency can be doubled [15] by applying additional light out-coupling measures.…”
Section: Properties Of State Of the Art Organic Light Emitting Diodesmentioning
confidence: 99%
“…Outcoupling efficiency can be calculated with the aid of advanced modeling techniques 14-16 which show that only approximately 20-30% of emitted photons escape a noncavity planar OLED fabricated on a conventional glass substrate. [17][18][19] Hence, in order to fully convert the input electrical power into optical power, it is essential to overcome this low outcoupling efficiency.It should be noted that two factors are closely associated with typically low OLED outcoupling efficiency: the planarity of the device and refractive indices of the thin film stack. A planar organic/metal interface leads to evanescently coupled surface plasmonic losses, 20 while an index gradient starting from high-index organic layers to mid-index glass substrate to low-index ambient air leads to laterally travelling waveguided and substrate-trapped loss modes.…”
mentioning
confidence: 99%
“…Outcoupling efficiency can be calculated with the aid of advanced modeling techniques 14-16 which show that only approximately 20-30% of emitted photons escape a noncavity planar OLED fabricated on a conventional glass substrate. [17][18][19] Hence, in order to fully convert the input electrical power into optical power, it is essential to overcome this low outcoupling efficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 However, for white emission, light outcoupling needs to be optimized for all colors, and therefore, thinner Ag layers with high transmission over a broad wavelength regime are essential. [16][17][18] We have previously demonstrated that a wetting layer comprised of a few nanometers of gold (Au) enables formation of ultrathin Ag electrodes that show excellent performance as top-electrodes of white inverted and non-inverted top-emitting OLEDs, and top-illuminated organic solar cells. [19][20][21] However, the replacement of the ITO bottom anode by such composite ultrathin electrodes has not been studied before.…”
mentioning
confidence: 99%